MUC4 expression by immunohistochemistry is a specific marker for BCR-ABL1+ and BCR-ABL1-like B-lymphoblastic leukemia. Issue 6 (12th May 2022) - Kaumeyer, Benjamin; Fidai, Shiraz; Sukhanova, Madina; Yap, Kai Lee; Segal, Jeremy; Raca, Gordana; Stock, Wendy; McNeer, Jennifer; Lager, Angela M.; Gurbuxani, Sandeep
Abstract: BCR-ABL1 -like B-acute lymphoblastic leukemia (B-ALL) is a genetically heterogeneous group of high-risk B-ALL that benefits from targeted tyrosine kinase inhibitor (TKI) therapy. The incidence of this high-risk B-ALL is relatively low and screening with surrogate markers will be useful to identify patients for further genetic testing. Here we demonstrate that widely available MUC4 protein immunohistochemistry (IHC) is predictive of a BCR-ABL1 -like genotype for a subset of patients. Overall, MUC4 expression was observed in 36% (9/25) BCR-ABL1 -like, 43% (3/7) BCR-ABL1 + and 9% (2/22) B-ALL other cases ( p =.019 for BCR-ABL1 like and BCR-ABL1 + versus B-ALL others). Furthermore, 83% (5/6) of patients with ABL class fusions showed MUC4 expression when compared to 25% (4/16, p =.006) patients with JAK class fusions. Overall, the study demonstrates that MUC4 expression is highly specific (90.9%) for BCR-ABL1 + and BCR-ABL1 -like B-ALL with high sensitivity for cases with ABL class fusions.